Comparison between single point versus double point injection in supraclavicular block incidence: ulnar sparing - S., Pooja; Anil, Devika; M. S., Nishana (International Journal of Research in Medical Sciences, 2025)
Background: This study compared the efficacy of single-point versus double-point injection techniques in ultrasound-guided supraclavicular brachial plexus blocks, focusing on success rate, procedural time, onset and duration of sensory and motor block, and complications. Methods: Twenty patients (20-80 years) undergoing forearm surgery over one hour were randomized into two groups. Group D received 20 ml of 0.5% bupivacaine divided into two 10 ml injections (superior cluster and inferior corner pocket). Group S received the entire 20 ml in the superior cluster pocket. Ultrasound guidance was used to locate the brachial plexus. Sensory and motor blockade onset were assessed by pinprick test and Bromage scale. Procedural time was recorded from ultrasound scanning to drug administration completion. Duration of blockade and adverse events were also noted. Results: Group D showed a significantly higher success rate (p<0.0001) and longer procedural time compared to group S. Onset of sensory and motor block was faster, and duration was significantly prolonged in group D. Conclusions: Double-point injection results in faster onset, longer duration, and higher success rate of supraclavicular blocks compared to single-point injection, but requires more procedural time.